QOLP-21. THE RELATIONSHIP BETWEEN CAREGIVING BURDEN AND ANXIETY SYMPTOMS IN CAREGIVERS OF PATIENTS WITH MALIGNANT GLIOMAS. (5th November 2018) - Quain, Katharine; Nipp, Ryan; Greer, Joseph; El-Jawahri, Areej; Batchelor, Tracy; Temel, Jennifer; Forst, Deborah
Abstract: BACKGROUND: Patients with malignant gliomas have a poor prognosis and high symptom burden. Caregivers of these patients face significant challenges due to the impact of the cancer on their loved ones neurological and mental faculties. We have previously shown that rates of clinically significant anxiety symptoms in caregivers of this population are high (50%). We sought to evaluate whether caregiving burden was associated with anxiety symptoms in caregivers of patients with malignant gliomas. METHODS: We conducted a prospective study in patients with newly diagnosed malignant gliomas and their caregivers, collecting caregivers self-report data within 6 weeks of diagnosis. We assessed caregivers anxiety symptoms with the Hospital Anxiety and Depression Scale, with subscale scores >7 considered clinically significant. We evaluated caregiving burden using the Caregiver Reaction Assessment (CRA) subscales, with the following domains: impact on schedule, caregivers esteem, lack of family support, impact on health, and impact on finances. We used a linear regression model to identify associations between the CRA subscales and anxiety symptoms. RESULTS: Fifty percent (38/76) of caregivers experienced clinically significant anxiety symptoms. Caregiving burden was significantly associated with anxiety symptoms F(5, 69)=11.525, p<0.001, R^2=0.455. Impact on schedule (B=2.273, p<0.001), impact on health (B=2.177, p=0.011), and impact on finances (B=1.374, p=0.002) added significantly to the model. CONCLUSIONS: Half of caregivers of patients with malignant gliomas experience clinically significant anxiety symptoms within 6 weeks of the patients diagnosis. Caregiving burden accounted for a substantial proportion (45.5%) of the variance in anxiety symptoms, with impact on the caregivers schedule, health, and finances demonstrating significant relationships with anxiety. These results suggest that caregivers who report a greater caregiving burden that impacts their schedule, health, and finances are also at risk for heightened anxiety symptoms. Interventions to reduce caregiving burden and decrease caregiver anxiety are needed.